Narrative Approaches in Character Education: Stories as a Medium of Moral and Ethical Learning - Desy Anindia Rosyida; Jamil Khan; Ida Wahyu Wijayati; Feby Arief Nugroho; Khalil Zaman (International Journal of Educational Narratives, 2025)
Background. Character education has increasingly emphasized the need for approaches that move beyond prescriptive moral instruction toward more experiential and reflective forms of ethical learning. Purpose. This study investigates how narrative approaches particularly storytelling and personal narratives can serve as effective mediums for developing moral reasoning, empathy, and ethical awareness among students. Method. The research aims to explore the pedagogical role of stories in fostering internalized moral values and to analyze how narrative engagement influences students’ ethical reflection and behavioral choices. Employing a qualitative case study design, data were collected through classroom observations, teacher interviews, and analysis of students’ reflective writings across three secondary schools implementing story-based character education programs. Results. The findings indicate that narrative pedagogy enables students to connect moral principles with lived experience, encourages perspective-taking, and stimulates dialogical moral reasoning. Stories functioned as ethical mirrors, allowing students to examine moral dilemmas within familiar contexts while developing emotional resonance with diverse human experiences.   Conclusion. The study concludes that storytelling is not only a didactic tool but also a transformative medium that cultivates ethical imagination, empathy, and critical reflection, making it essential to holistic character education.